Gorgias' apatē, Sophocles' Electra, and cognitive criticism - Grethlein, Jonas (Minds on stage, 2023)
This chapter offers a fresh look at the false messenger scene in Sophocles’ Electra through the combined lenses of ancient criticism and cognitive studies. In a first step, it contends that the claims of Gorgias fr. B 23 DK correspond with insights of cognitive accounts of aesthetic experience. In its main part, the chapter reconsiders Electra in the light of Gorgias fr. B 23 DK, suggesting that the false messenger speech stages the entwinement of deception with aesthetic illusion with which Gorgias fr. B 23 DK plays. It is first shown that the messenger speech is geared towards generating a strong aesthetic illusion. Then it is argued that the very devices that serve to engross the theatre audience are simultaneously a means of deception within the play. As pointed out in the conclusion, this association of aesthetics with ethics reveals a specifically ancient approach and sheds light on the limits as well as the benefits of employing cognitive studies in classics.
"apatē" ist im Titel in griechischen Buchstaben geschrieben
Gesehen am 17.07.2024